(untitled) (Acta Entomológica Chilena, 2022)
The seasonal cycle of Callisphyris macropus Newman (Coleóptera: Cerambyddae), under field conditions is described in this árdele. Samples were obtained from commercial plots of gooseberry, blaek currant and red currant in the IX and X Región, Chile. In currant, C macropus presents a biennial cycle. Ethological aspeets of oviposidon and larval behaviour in Ribes nigrum are indicated.